Pengaruh Hypnotherapi terhadap Pengurangan Nyeri Primer Menstruasi pada Mahasiswi Poltekkes Kemenkes Palembang Jurusan Keperawatan - Nur Purnama Sari; Ramesia Ratnawati; Satra Yunola; Helni Anggraini (Lembaga Pengembangan Kinerja Dosen, 2025)
Women who are experiencing menstruation, Menstrual Pain felt. These events can cause trauma because of the pain that had befallen him. The primary pain of menstruation can be reduced with one pharmacological methods namely Hypnotherapi. To know the influence of the Hypnotherapi against the reduction of the primary pain of menstruation at Coed poltekkes kemenkes Nursing Department in Palembang. The design used is posttes-group pretest design, research conducted on campus nursing poltekkes kemenkes palembang March 7, s. d. 18 March 2019. The population of this research is all a Nursing Sorority experience pain primer Mnstruasi. The selection of the sample with the Accidental Sampling techniques, where the samples that give as much intervention 30 people. This research data taken using sheet VDS. After the data tabulated, analyzed using the Wilcoxon signed rank test test with error rate α = 0.05. Based on research conducted showed that prior to the granting of Hypnotherapi (86.7%) and (80%) the respondents experienced moderate pain. After being given Hypnotherapi the majority (80%) the respondents suffered mild pain. Of the test being performed then obtained significant value at Hypnotherapi (p value = 0.000) so that a p value 0.05 <. There is the influence of the Hypnotherapi against the reduction of the primary pain of menstruation at Coed poltekkes kemenkes Palembang year 2019. Refer to the results of this research are the health workers especially midwives always provide motivation and Hypnotherapy treatment on a Coed primary menstrual pain experienced pain so that primary menstrual periods can be reduced.